A high-quality reference genome for the fish pathogen Streptococcus iniae. Issue 3 (1st March 2022) - Alsheikh-Hussain, Areej S.; Ben Zakour, Nouri L.; Forde, Brian M.; Silayeva, Oleksandra; Barnes, Andrew C.; Beatson, Scott A.
Abstract : Fish mortality caused by Streptococcus iniae is a major economic problem in aquaculture in warm and temperate regions globally. There is also risk of zoonotic infection by S. iniae through handling of contaminated fish. In this study, we present the complete genome sequence of S. iniae strain QMA0248, isolated from farmed barramundi in South Australia. The 2.12 Mb genome of S. iniae QMA0248 carries a 32 kb prophage, a 12 kb genomic island and 92 discrete insertion sequence (IS) elements. These include nine novel IS types that belong mostly to the IS 3 family. Comparative and phylogenetic analysis between S. iniae QMA0248 and publicly available complete S. iniae genomes revealed discrepancies that are probably due to misassembly in the genomes of isolates ISET0901 and ISNO. Long-range PCR confirmed five rRNA loci in the PacBio assembly of QMA0248, and, unlike S. iniae 89353, no tandemly repeated rRNA loci in the consensus genome. However, we found sequence read evidence that the tandem rRNA repeat existed within a subpopulation of the original QMA0248 culture. Subsequent nanopore sequencing revealed that the tandem rRNA repeat was the most prevalent genotype, suggesting that there is selective pressure to maintain fewer rRNA copies under uncertain laboratory conditions. Our study not only highlights assembly problems in existing genomes, but provides a high-quality reference genome for S. iniae QMA0248, including manually curated mobile genetic elements, that will assist future S. iniae comparative genomic and evolutionary studies.